\(\sqrt{x}-\sqrt{y}\))

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 7 2021

\(x-y-3\left(\sqrt{x}-\sqrt{y}\right)=\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}\right)-3\left(\sqrt{x}-\sqrt{y}\right)\)

\(=\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}-3\right)\)

14 tháng 10 2018

Q= [\(\frac{\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}\right)}{\sqrt{x}-\sqrt{y}}+\frac{\left(\sqrt{x}-\sqrt{y}\right)\left(x+\sqrt{xy}+y\right)}{\left(\sqrt{y}-\sqrt{x}\right)\left(\sqrt{y}+\sqrt{x}\right)}\)]\(:\frac{x-2\sqrt{xy}+y+\sqrt{xy}}{\sqrt{x}+\sqrt{y}}\)

\(Q=\left(\sqrt{x}+\sqrt{y}-\frac{x+\sqrt{xy}+y}{\sqrt{x}+\sqrt{y}}\right):\frac{x-\sqrt{xy}+y}{\sqrt{x}+\sqrt{y}}\)

\(Q=\frac{x+2\sqrt{xy}+y-x-\sqrt{xy}-y}{\sqrt{x}+\sqrt{y}}.\frac{\sqrt{x}+\sqrt{y}}{x-\sqrt{xy}+y}\)

\(Q=\frac{\sqrt{xy}}{x-\sqrt{xy}+y}\)

15 tháng 10 2018

phan 3 nua

3 tháng 9 2018

a) ta có : \(\dfrac{x\sqrt{x}-y\sqrt{y}}{\sqrt{x}-\sqrt{y}}=\dfrac{\left(\sqrt{x}-\sqrt{y}\right)\left(x+\sqrt{xy}+y\right)}{\sqrt{x}-\sqrt{y}}=x+\sqrt{xy}+y\)

b) ta có : \(\dfrac{x-\sqrt{3x}+3}{x\sqrt{x}+3\sqrt{3}}=\dfrac{x-\sqrt{3x}+3}{\left(\sqrt{x}+\sqrt{y}\right)\left(x-\sqrt{3x}+3\right)}=\dfrac{1}{\sqrt{x}+\sqrt{y}}\)

14 tháng 9 2019

a) \(\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)\)

\(=\sqrt{x}\left(x+\sqrt{x}+1\right)-1\left(x+\sqrt{x}+1\right)\)

\(=x\sqrt{x}-1\)

31 tháng 5 2017

\(=\frac{\sqrt{xy}\left(\sqrt{x}-\sqrt{y}\right)}{\sqrt{xy}}+\frac{\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}\right)}{\left(\sqrt{x}-\sqrt{y}\right)}\)

\(=\left(\sqrt{x}-\sqrt{y}\right)+\left(\sqrt{x}+\sqrt{y}\right)\)\(=2\sqrt{x}\)

31 tháng 5 2017

bạn nhòm à

15 tháng 7 2016

b) \(\frac{2-\sqrt{2}}{\sqrt{2}}=\frac{\left(2-\sqrt{2}\right)\sqrt{2}}{\sqrt{2}\cdot\sqrt{2}}=\frac{2\sqrt{2}-2}{2}=\frac{2\left(\sqrt{2}-1\right)}{2}=\sqrt{2}-1\)

17 tháng 7 2016

a. \(\left(\sqrt{5-2\sqrt{6}}+\sqrt{2}\right).\sqrt{3}=\left(\left|\sqrt{3}-\sqrt{2}\right|+\sqrt{2}\right).\sqrt{3}=\left(\sqrt{3}\right)^2=3\)

17 tháng 7 2016

b.\(\frac{2-\sqrt{2}}{\sqrt{2}}=\frac{\sqrt{2}\left(2-\sqrt{2}\right)}{2}=\frac{2\sqrt{2}-2}{2}=\frac{2\left(\sqrt{2}-1\right)}{2}=\sqrt{2}-1\)